2020
DOI: 10.1002/eji.201948288
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐CD52 blocks EAE independent of PD‐1 signals and promotes repopulation dominated by double‐negative T cells and newly generated T and B cells

Abstract: Lymphocyte depletion using anti‐CD52 antibody effectively reduces relapses of multiple sclerosis (MS). To begin to understand what mechanisms might control this outcome, we examined the effect of a murine‐CD52‐specific mAb on the depletion and repopulation of immune cells in mice with experimental autoimmune encephalomyelitis (EAE), a model of MS. We tested whether the tolerance‐promoting receptor programmed cell death protein‐1 (PD‐1) is required for disease remission post anti‐CD52, and found that PD‐1‐defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…Moreover, recent findings show that also CD8 double-negative (DN) T cells are hyper-repopulated after alemtuzumab treatment in EAE mice. DN T cells have frequently been associated with suppression of immune responses, highlighting another possible mechanism to suppress autoimmunity beside the action of Treg cells [22].…”
Section: Alemtuzumab For the Treatment Of Ms: Preclinical Studies In mentioning
confidence: 99%
“…Moreover, recent findings show that also CD8 double-negative (DN) T cells are hyper-repopulated after alemtuzumab treatment in EAE mice. DN T cells have frequently been associated with suppression of immune responses, highlighting another possible mechanism to suppress autoimmunity beside the action of Treg cells [22].…”
Section: Alemtuzumab For the Treatment Of Ms: Preclinical Studies In mentioning
confidence: 99%
“…EAE was induced and scored as previously described ( Haile et al, 2020 ) using MOG 35–55 peptide in complete Freund's adjuvant and pertussis toxin. EAE disease was scored as 0 = no signs, 1 = paralyzed tail, 2 = hindlimb weakness, 3 = paralysis of both hindlimbs, 4 = paralysis of both hindlimbs and weakness of one forelimb, 5 = moribund.…”
Section: Methodsmentioning
confidence: 99%
“…The hematopoietic stem cells and lymphocyte precursor cells lack CD52, thereby providing the potential for lymphocyte repopulation from precursors after anti-CD52 therapy. We recently showed that immune system reset with anti-CD52 promotes lymphocyte repopulation that is initially dominated by double-negative T cells and newly generated T and B cells ( Haile et al, 2020 ). The rapid repopulation of the peripheral lymphoid niche with newly generated T cells in mice with EAE treated with anti-CD52 suggested a possible explanation for the variable efficacy of anti-CD52 in humans ( Cohen et al, 2012 ; Haile et al, 2020 ; Turner et al, 2015 ; Ziemssen and Thomas, 2017 ) compared to the near-complete effectiveness in mice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations